The Spanish Immigrant Joseph Martín de Fuentes: A Self-Styled Reformer, Imperial Watchdog and Nativist in Puerto Rico at the en of the Eighteenth Century - Jorge Chinea (Universidad de Quintana Roo, 2001)
One of the principal goals of the Bourbon reforms was the development of unexploited spaces in Spanish America. Due to the insufficiency of metropolitan settlers in the islands of Trinidad and Puerto Rico, after 1776 the Bourbons authorized foreign colonists from friendly Catholic nations to settle in both colonies. This paper traces the experiences of one Spanish immigrant, Joseph Mart’n de Fuentes and his futile yearlong attempt to compel Jayme OÕDaly, the Irish Director of several themes of interests to scholars of the Bourbon reforms, such as immigration, economic development, government corruption, and the rise of colonial Žlites.